Studies on biochemical changes in the uterine fluid of repeat breeding crossbred cows - SHUKLA, S P; SHARMA, R D (The Indian Journal of Animal Reproduction, 2023)
Biochemical changes in the uterine fluid of IO normal and 45 repeat breeding cows were determined. Studies in the uterine fluid indicated significantly higher levels of total protein and inorganic phosphorus in normal cows compared to repeat breeding cows. The pH value of uterine fluid was significantly higher in repeat breeders normal cows. The levels of calcium, magnesium, copper and zinc were similar in both the groups.